Language choice in enquiries about accommodation in hotel telephone service encounters - Ting , Su Hie; Mahadhir, Mahanita; Ting , Sing Yea (2010)
Service encounters are complementary in that one interactant demands and another gives, resulting in much shorter but more formal conversations than everyday talk. In multilingual settings, the interest is not only in the staging of the service encounter but also the language choices used to fulfil various functions in the transaction, The study examined language choice in enquiries about accommodation in hotel telephone service encounters. The specific aspects studied were the staging of the telephone enquiries about hotel accommodation and the points ofdeparture from the initial language used for the telephone enquiry by the client and the hotel receptionist. The case study involved a trained hotel receptionist working in a three-star hotel. Her interactions with the clients were audio-taped with the permission of the hotel management. Analysis of the staging of the hotel accommodation enquiry was carried out using Halliday and Hassan's (1985) framework of the structure of service encounters. The analysis of 21 accommodation enquiries showed conformity to the Greeting ^Service Initiation ^Service Request ^Service Compliance ^Service Closure. The recursive elements were the stages of Service Request, Service Compliance and Service Closure. Analysis from the aspect of language choice indicated that English was the nonnative choice in handling enquiries about hotel accommodation. It is usually the client who initiated code-switching to other languages such as Bahasa Melayu and Mandarin. The study showed that in service encounters, the fonnality of the situation dictated the initial use of English despite the societal nonn of using the shared language when communication with those from the same language background, often evident in the accent and pronunciation of words